The Analysis of the Impact of Implementing Sharia Business Ethics on Customer Loyalty in the Arjosari Traditional Market, Pacitan Regency - Hidayatulloh, Muhammad Nur; Syaiful Ma’ruf; Asis Sustiawan (Institut Muslim Cendekia, 2025)
This study seeks to examine how Islamic business ethics are implemented in purchasing and selling activities at the Arjosari traditional market in Pacitan Regency. This research is driven by the noted absence of business ethics implementation in the Arjosari traditional market. Integrity, friendliness, courtesy, and equity are fundamental tenets of Islamic business ethics; Preliminary observations suggest that some vendors may engage in practices perceived as dishonest, unapproachable, or inconsistent in pricing, raising concerns about the application of Islamic business ethics in the market. Customers often associate satisfaction with merchants perceived to uphold Islamic business ethics, suggesting a potential link worth exploring. Consequently, business actors must implement sharia business ethics, regardless of whether they are operating in micro or macro enterprises. This research utilizes a qualitative method to investigate the experiences and viewpoints of traders and customers concerning Islamic business ethicsThe study’s findings indicate that participants perceive Islamic business ethics as contributing to increased customer loyalty and trust in market transactions.